2010
DOI: 10.1080/15287391003751745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gestational and Lactational Fenvalerate Exposure on Immune and Reproductive Systems of Male Rats

Abstract: The aim of this study was to determine the consequent reproductive developmental and immunotoxic effects due to exposure to fenvalerate during pregnancy and lactation in male offspring of maternal-treated rats. Pregnant rats were treated daily by oral gavage with 40 or 80 mg/kg of fenvalerate or corn oil (vehicle, control), from d 12 of pregnancy to d 21 of lactation. Immune and reproductive developmental effects were assessed in male offspring at postnatal days (PND) 40 (peripuberty), 60 (postpuberty), and 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 49 publications
0
18
0
2
Order By: Relevance
“…Several studies have been conducted to evaluate the reproductive toxicity of pesticides in mammals. Some pesticides that induce reproductive toxicity are: dimethoate (Verma and Mohanty, ), fenvalerate (Arena et al, ; Nassr et al, ), dichlorvos (Diricana and Kalender, ), propetamphos (Ismail and Al‐Taher, ), glyphosate (Romano et al, ), among others. Reproductive toxicity studies should be conducted as part of the toxicity evaluation of any compound, which complements the systemic toxicity tests (Dalsenter et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the reproductive toxicity of pesticides in mammals. Some pesticides that induce reproductive toxicity are: dimethoate (Verma and Mohanty, ), fenvalerate (Arena et al, ; Nassr et al, ), dichlorvos (Diricana and Kalender, ), propetamphos (Ismail and Al‐Taher, ), glyphosate (Romano et al, ), among others. Reproductive toxicity studies should be conducted as part of the toxicity evaluation of any compound, which complements the systemic toxicity tests (Dalsenter et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Three nonconsecutive sections (5 μm thick) per animal, separated by 100 μm distance, were obtained, mounted on glass slides, and stained with H&E. The histological evaluation of organs was accomplished quantitatively for testis and qualitatively for epididymis under a light microscope following specific guidelines for toxicological studies (Foley, ). Nuclei of Sertoli cells were counted in 20 cross‐sections of seminiferous tubules per rat, under a light microscope, at 400× magnification (Nassr et al, , with modifications).…”
Section: Methodsmentioning
confidence: 99%
“…After the 2001 U.S. EPA voluntary phaseout of residential OP use, pyrethroids have become the principal pesticide class used for indoor pest control (Sudakin 2006), creating opportunities for dermal, inhalation, and incidental ingestion exposures (Agency for Toxic Substances and Disease Registry 2003). In addition to acute poisonings, epidemiological studies have reported evidence of neurotoxic and developmental effects from OP exposures (Bouchard et al 2010; Harley et al 2011; Rauh et al 2011) and evidence of reproductive toxicity (Meeker et al 2008; Nassr et al 2010) and endocrine disruption (Han et al 2008; Meeker et al 2009) associated with pyrethroid exposures. In addition, the U.S. EPA has listed permethrin, a widely used pyrethroid for both agricultural and residential insect control, as “likely to be carcinogenic to humans” (U.S.…”
Section: Introductionmentioning
confidence: 99%